Principal Leadership Ethics as A Role Model in High School - Amiruddin Siahaan; Aswaruddin Aswaruddin; Maulidayan Maulidayan; Ahmad Zaki; Novita Sari; Arief Aulia Rahman (STAI Hubbulwathan Duri, 2023)
Exemplary leadership is a crucial factor in a leader's success. As a leader, the school principal plays a significant role in setting an example for teachers. However, whether this aspiration has been fulfilled remains an area that requires further research. This study explores the ethical leadership of school principals who serve as role models. The research approach adopted for this scientific article is a literature review involving data collection, reading, and managing research materials from various sources. The study's findings highlight leaders' pivotal role in shaping ethical behaviour and fostering an ethical climate within organizations. The leader's strategic approach to promoting ethical conduct becomes integral to the overall organizational strategy. In this context, the ethical mindset of managers revolves around three core concepts: leading by example through concrete actions, utilizing rewards and discipline, and actively communicating about ethics and values.In conclusion, one of the critical responsibilities of a leader is to cultivate a positive ethical climate within the organization. The ethical climate represents the perception of organizational members, leaders, and subordinates concerning the organization's adherence to ethical principles and the prevailing internal environment. Further research in this area can shed more light on the impact of exemplary leadership on organizational ethics.